2004
DOI: 10.1179/096797804225018705
|View full text |Cite
|
Sign up to set email alerts
|

Self-formed mullite containing refractory barium silicate cements and their castable applications

Abstract: Six batches consisting of different percentages of barite, kaolin and calcined alumina were sintered at 1500-1600uC for 3 h to produce self-formed mullite containing barium silicate cements. The compositions of the cement mixes were investigated using X-ray diffraction. Physicomechanical, sintering and refractory properties were tested according to standard specifications. Each of the mixes, composed mainly of varying proportions of mullite and dibarium silicate minerals, showed different behaviour. The best c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…This in turns leads to a noticeable improvement in sintering parameters. After firing at 1550 8C the amount of CA 6 increases causing a further stress on the matrix resulting in a loosening in the structure (relieve) and hence a noticeable decrease in sintering parameters, in case of mixes 1, 2 and 3 this occurs at 1500 8C by the action of CA or CA 2 phases [29]. Fig.…”
Section: Densification Parametersmentioning
confidence: 97%
“…This in turns leads to a noticeable improvement in sintering parameters. After firing at 1550 8C the amount of CA 6 increases causing a further stress on the matrix resulting in a loosening in the structure (relieve) and hence a noticeable decrease in sintering parameters, in case of mixes 1, 2 and 3 this occurs at 1500 8C by the action of CA or CA 2 phases [29]. Fig.…”
Section: Densification Parametersmentioning
confidence: 97%
“…12) shows the reappearance of orthorhombic and euhedral and subhedral crystals of barium silicate in addition to monoclinic and hexagonal-barium aluminium silicates. 17 Similarly, the SEM of composition F5 (cf. Fig.…”
Section: Morphology Of Powdered Sintered Shielding Materials Compositionsmentioning
confidence: 99%
“…mullite and highly reactive amorphous aluminosilicate vitreous as major mineralogical phases apart from the quartz, the fly ash can be used as a potential resource starting materials for making barium containing radiopaque celsian glass ceramics, 8 refractory cements such as, barium silicate, barium aluminate. 17,18 It is reported that barium aluminate is being used as an indispensable component in the Portland cement mixture and as a fundamental materials in the construction of nuclear reactors. 19 Recently, an environmental barrier multi-layer coating has also been developed based on a composition containing celsian, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…These results support our conclusions on the previous work [22] regarding the improvement in physicomechanical properties of the prepared ceramic bodies especially the mixes CM3 and CM4 at 1500 o C due to the presence of recognized assemblage of minerals namely; mullite (3Al2O3.2SiO2), aluminate, barium aluminate (BaO.Al2O3) and corundum (Al2O3) system [22].These formed minerals (proved before with XRD and SEM [22]) are characterized with good mechanical properties,(they interacted together forming a compact rod-like crystals of mullite interacted with patch crystals of barium aluminate while the hexagonal plate-like turned together from one side with the other minerals on the other leading to a well compact microstructure and hence less pores and cavities in the matrix causing on improvement in volume stability (low linear shrinkage), a relatively higher bulk densities, lower apparent porosity and hence good recognized mechanical strength [28][29][30][31][32][33][34][35].…”
Section: Anovamentioning
confidence: 99%